Perlindungan Hukum Korban Perundungan dan Urgensi Pencegahannya Bagi Masyarakat (Studi Kasus Perundungan Siswa SD) - Jasmine Dameria Gultom; Latricia Tiara Putri; Nadhira Imaniyar; Inayatu Dzil Izzati; Marsya Arviela Maharani; Tigor Akhmad Fahrhezi; Mulyadi M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The number of cases of child abuse has become increasingly alarming and disturbing recently. Abuse is a well-known phenomenon in Indonesia and abroad. The parties are usually school age and bullying currently continues in elementary to secondary schools, bullying also continues in college, although on a relatively small scale. The type of research used in this study is normative legal research. Data processed by this method are primary, secondary and tertiary data. Therefore the problems discussed in this study used approaches related to the legal norms contained in the law. Research results show that legal protection is regulated by Child Protection Act No. 1. 23/02/2012 and Child Justice Act No. 23/2002/2012. 11th of 2012.Â